Cape Verdean Kriolu as an Epistemology of Contact - Pardue, Derek (2012)
Kriolu as language and sentiment represents a “contact perspective”, an outlook on life and medium of identification historically structured by the encounter. Cape Verde was born out of an early creole formation and movement is an essential part of Cape Verdean practices of language and identity. Most recently, the Portuguese state and third-party real estate developers have provided another scenario in the long series of (dis)emplacement dramas for Cape Verdeans as Lisbon administrations have pushed to demolish “improvised” housing and regroup people into “social” neighborhoods. I argue that neighborhoods such as Casal da Boba are not simply “contact zones” where differences are made manifest and subaltern agency is potentially given a stage. In the case of Cape Verdean Kriolu in Lisbon, the concept of “contact” is an epistemological one. This essay connects the empirical realities of Lisbon neighborhoods to the historically structured experiences of contact vis-à-vis colonialism, migration and language.